Does 18F-Fluorocholine PET/CT add value to positive parathyroid scintigraphy in the presurgical assessment of primary hyperparathyroidism? - Imperiale, Alessio; Bani, Jacob; Bottoni, Gianluca; Latgé, Adrien; Heimburger, Céline; Catrambone, Ugo; Vix, Michel; Treglia, Giorgio; Piccardo, Arnoldo (Frontiers in Medicine, 2023)
Introduction To investigate the value of presurgical 18F-FCH PET/CT in detecting additional hyperfunctioning parathyroids despite a positive 99mTc-sestamibi parathyroid scintigraphy in patients with primary hyperparathyroidism (pHPT). Methods This is a retrospective study involving patients with pHPT, positive parathyroid scintigraphy performed before 18F-FCH PET/CT, and parathyroid surgery achieved after PET/CT. Imaging procedures were performed according to the EANM practice guidelines. Images were qualitatively interpreted as positive or negative. The number of pathological findings, their topography, and ectopic location were recorded. Histopathology, Miami criterion, and biological follow-up were considered to ensure effective parathyroidectomy confirming the complete excision of all hyperfunctioning glands. The impact of 18F-FCH PET/CT on therapeutic strategy was recorded. Results 64/632 scanned pHPT patients (10%) were included in the analysis. According to a per lesion-based analysis, sensitivity, specificity, positive predictive value, and negative predictive value of 99mTc-sestamibi scintigraphy were 82, 95, 87, and 93%, respectively. The same values for 18F-FCH PET/CT were 93, 99, 99, and 97%, respectively. 18F-FCH PET/CT showed a significantly higher global accuracy than 99mTc-sestamibi scintigraphy: 98% (CI: 95–99) vs. 91% (CI: 87–94%). Youden Index was 0.79 and 0.92 for 99mTc-sestamibi scintigraphy and 18F-FCH PET/CT, respectively. Scintigraphy and PET/CT were discordant in 13/64 (20%) patients (49 glands). 18F-FCH PET/CT identified nine pathologic parathyroids not detected by 99mTc-sestamibi scintigraphy in 8 patients (12.5%). Moreover, 18F-FCH PET/CT allowed the reconsideration of false-positive scintigraphic diagnosis (scinti+/PET-) for 8 parathyroids in 7 patients (11%). The 18F-FCH PET/CT influenced the surgical strategy in 7 cases (11% of the study population). Conclusion In a preoperative setting, 18F-FCH PET/CT seems more accurate and useful than 99mTc-sestamibi scan in pHPT patients with positive scintigraphic results. Positive parathyroid scintigraphy could be not satisfactory before neck surgery particularly in patients with multiglandular disease, suggesting a need to evolve the practice and define new preoperative imaging algorithms including 18F-FCH PET/CT at the fore-front in pHPT patients.